Encyclopedia of Drug Metabolism and Interactions 2012
DOI: 10.1002/9780470921920.edm029
|View full text |Cite
|
Sign up to set email alerts
|

Mass Balance Studies in Animals and Humans

Abstract: Before first‐in‐human (FIH) studies with a new drug candidate, preclinical studies need to be conducted to fulfill regulatory requirements or to facilitate regulatory approval. In the United States, investigational new drug (IND) applications with the Food and Drug Administration (FDA) may include IND enabling studies, such as (i) in vitro and in vivo pharmacology studies for intended use, (ii) toxicology studies supporting the starting dose and duration of an FI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In human, the absorption of midostaurin was rapid after oral administration in a diluted microemulsion, with the average peak plasma concentration of total radioactivity observed between 1 and 3 hours postdosing. The extent of oral absorption can be estimated when radiolabeled drug is administered (Lin, et al, 2012). Midostaurin oral absorption was estimated to be high, because only 3.43% of unchanged midostaurin was found in the feces (Table 4) and midostaurin was confirmed to be stable in the in vitro fecal incubation study (Novartis data on file).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In human, the absorption of midostaurin was rapid after oral administration in a diluted microemulsion, with the average peak plasma concentration of total radioactivity observed between 1 and 3 hours postdosing. The extent of oral absorption can be estimated when radiolabeled drug is administered (Lin, et al, 2012). Midostaurin oral absorption was estimated to be high, because only 3.43% of unchanged midostaurin was found in the feces (Table 4) and midostaurin was confirmed to be stable in the in vitro fecal incubation study (Novartis data on file).…”
Section: Resultsmentioning
confidence: 99%
“…Midostaurin oral absorption is high (.90%), because only 3.43% of intact drug was found in the feces (Table 4), which was likely unabsorbed drug because midostaurin is stable in the gastrointestinal milieu. Preclinical studies also showed high absorption in rats (.90%) (Supplemental Material), and the rat is a predictive and commonly used model of absorption in humans (Chiou and Barve, 1998;Lin, et al, 2012). Because midostaurin is a lipophilic drug (cLogP .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation